Unilateral orolingual angioedema in a patient with sarcoidosis after intravenous thrombolysis due to acute stroke without improvement after treatment with icatibant. Issue 12 (21st December 2020) - Wollmach, Anna Daniela; Zehnder, Daniel; Schwendinger, Markus; Tarnutzer, Alexander Andrea
Abstract : A potential complication after intravenous administration of recombinant tissue plasminogen activators (rtPAs) for thrombolysis in acute ischaemic stroke is orolingual angioedema, with an incidence of 0.4%–7.9%. In the herewith reported case, we discuss potential links between a history of sarcoidosis and the occurrence of orolingual angioedema after rtPA administration. Sarcoidosis is often accompanied by an elevated ACE level. In contrast, low ACE levels appear to play a role in the pathomechanism currently assumed to trigger angioedema, that is, the activation of the bradykinin and complement pathways. Medication with ACE inhibitors is considered a risk factor for angioedema. Based on these considerations, the patient was also treated with icatibant, a bradykinin B2-receptor antagonist, which has been found useful in recent publications on treating orolingual angioedema after intravenous lysis in ischaemic stroke.